Characterization of root diameter-water stress behaviour in epiphytes using dendrometer / Mohd Khairi Nordin ...[et al.] - Nordin, Mohd Khairi; Md Tahir, Nooritawati; Mohd Yassin, Ahmad Ihsan; Megat Ali, Megat Syahirul Amin (Universiti Teknologi MARA, 2021)
Water management and irrigation systems are vital to precision agriculture. Understanding of plant behaviour is critical for future deployment of such systems. This paper elaborates on the characterization of root diameter changes in commercial epiphytes under water stress condition. Two Vanda hybrids have been used in this study. Initially, consistency and linearity tests are performed on the dendrometers. The devices are then fixed to the root of the epiphytes. Subsequently, changes in root diameters, along with the surrounding temperature and humidity is then recorded by data loggers over a duration of two weeks, at every 15-minutes interval. The time-series data for root diameter, temperature, and humidity are analyzed. Changes to root diameter are well-captured, and the data plots have provided useful information related to the water status in roots. Parameters such as daily root shrinkage rate, maximum root minimum, and daily plots can be extracted from the recorded data. The information is useful for monitoring the quality of plant growth against changes in their needs for water.